A facile access for the synthesis of 1-hetero(aryl)-1, 2, 3-triazoles linked to equol under mild conditions. Issue 20 (17th October 2020) - Nibin Joy, Muthipeedika; Beliaev, Nikolai; Beryozkina, Tetyana V.; Bakulev, Vasiliy A.
Abstract: We herein report a convenient methodology for the synthesis of 1-hetero(aryl)-1, 2, 3-triazoles linked with equol by utilizing copper-catalyzed azide-alkyne cycloaddition reaction under exceptionally mild conditions. The salient features of this developed protocol include: easy isolation process, good to excellent yield of the products and appendage diversity of heteroaryl triazoles. Graphical Abstract: